2009
DOI: 10.5194/npg-16-1-2009
|View full text |Cite
|
Sign up to set email alerts
|

Solar wind interaction with the Earth's magnetosphere: the role of reconnection in the presence of a large scale sheared flow

Abstract: Abstract. The Earth's magnetosphere and solar wind environment is a laboratory of excellence for the study of the physics of collisionless magnetic reconnection. At low latitude magnetopause, magnetic reconnection develops as a secondary instability due to the stretching of magnetic field lines advected by large scale Kelvin-Helmholtz vortices. In particular, reconnection takes place in the sheared magnetic layer that forms between adjacent vortices during vortex pairing. The process generates magnetic islands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…In particular, secondary instabilities excited in the vortices have been proposed as candidates for transport of the SW plasma into the magnetosphere (e.g. Matsumoto and Hoshino, 2004;Califano et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, secondary instabilities excited in the vortices have been proposed as candidates for transport of the SW plasma into the magnetosphere (e.g. Matsumoto and Hoshino, 2004;Califano et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In that case, the reconnection occurring during the development of the Kelvin-Helmholtz instability is thus driven by the faster ideal instability. [18][19][20][21][22] APPENDIX: SLOW GROWTH REGIME Let us consider the slow growth regime, where ␥ / ␣FЈ͑0͒⑀ Ӷ 1, in the "comparable shear" regime, where ͉GЈ͑0͉͒ / FЈ͑0͒ϳ1. For the sake of simplicity, we take…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that the velocity field, generated by Kelvin-Helmholtz instability, is able to force the magnetic field lines to reconnect. [18][19][20][21][22] This reconnection is not an instability but is induced by the ideal Kelvin-Helmholtz instability. In fact, for a resistive plasma, the rate at which it happens is independent from the value of the resistivity and is related only to the Kelvin-Helmholtz growth rate.…”
Section: Comparable Shear Regimementioning
confidence: 97%
See 2 more Smart Citations